Critical Thinking Skills through Science Learning - Zoha Khan; Dr.Sadaf Zamir Ahmed (JSE, 2024)
Critical thinking skills in science learning at the elementary level are a topic of significant importance in educational research and practice. The problem addressed in this research is to determine whether science learning fosters the development of critical thinking skills among elementary-level students in various educational streams within Pakistan's capital city, including private schools and public sector schools. This remark emphasises the essential problem of whether critical thinking skills are adequately nurtured in students from varied educational backgrounds through science study. This study aims to look into the relationship between science learning and the development of critical thinking skills in the defined educational streams in the provided geographical setting. This study aims to see if there are differences in the level of critical thinking skills produced by science instruction across multiple educational streams. By enhancing critical thinking skills among elementary science students, the study contributes to the development of future generations equipped with the cognitive abilities critical for scientific literacy, problem-solving, and informed decision-making. Keywords: Critical Thinking, Science learning, Students, Elementary level.